Fish and makrophyta association in the swamp area in the Sawah Village, North Kampar Sub-district, Riau Province. - Merry Christina Naibaho; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThere are many types of makrophytaand fish in the swamp area in the Sawah Village, but there is no information on the association of makrophyta and fish in the swamp. To understand that association, a research has been conducted in August – September 2018. Sampling were conducted once /week for a month period. Puntius johorensis, Rasbora einthoveniiand Puntius lineatus were found around the community of Barclaya sp. Around the Hydrilla verticillatacommunity, there wereNandus nebulosus, R. einthovenii,Trichogaster trichopterus and Puntius johorensis. Around the Pistia stratiotes  community, there were T. trichopterus and  R. Einthovenii. While T. Trichopteruswas found around the Paspalum sp community. Even though the plants were different but the type of fish present was similar. Based on data obtained, it can be concluded that there wereno specific association between makrophyta and fish species in the swamp area in the Sawah Village. Keywords :  Makrophyta, Fish association, Blackwater swamp, Aquatic plant.